Research on the security orchestration and scheduling technology of the computing power network based on SRv6 + ARN - XI Zhuoning; HOU Huifang; PAN Jie; ZHAO Zhanjun; BU Zhonggui; YE Lan; CHEN Xi; XUE Zhao (Dianxin kexue)
Addressing key issues such as low efficiency of resource pool orchestration and scheduling, insufficient integration of cloud-network-security technologies in the current development of computing network security services, against the research background of the cloud-network-security collaborative innovation and operation pressure faced by operators in the security service market, a computing network security resource pool orchestration and scheduling technology system based on segment routing over IPv6 (SRv6)+ application responsive network (ARN）was proposed. Through in-depth integration of the SRv6 protocol, the research realizes end-to-end connectivity between the network and the service, and through ARN, it improved the simplicity of data plane identification and dynamic scheduling capabilities, constructing a network data plane with intelligent orchestration and scheduling capabilities to support the flexible combination and rapid deployment of security services. The research results mainly include the SRv6+ARN orchestration and scheduling technology architecture, key technologies, and reliability guarantees, providing technical support for operators to build a cloud-network-security collaborative computing network security resource pool.